Avaliação do efeito de diferentes relações DQO/N sobre o processo anammox e viabilidade da aplicação do processo como pós-tratamento de efluente de reator UASB tratando esgoto doméstico - Cintia Dutra Leal (2015)
Anaerobic oxidation of ammonia (Anammox) performed by anaerobic and chemolithoautotrophics bacteria, is a important pathway on the biological nitrogen cycle. The Anammox process has numerous advantages and has been successfully applied for nitrogen removal at various treatment plants around the world, primarily for the treatment of wastewater, rich in nitrogen. The presence of organic matter may cause adverse effects on the anammox bacteria, decreasing the efficiency or even causing inhibition of the anammox process. This study evaluated in the laboratory, the applicability and efficiency of removing ammonia nitrogen by Anammox process as post-treatment of anaerobic effluent from a UASB reactor treating domestic wastewater. The study was divided into three phases, Phase I comprises the cultivation period of the anammox biomass, in Phase II were tested the relations COD/N of 0.7, 1.4, 2.8, 3.5 and 5.0, using a solution of glucose as carbon source and Phase III in which the reactor was fed with real anaerobic effluent. A sequencing batch reactor with a volume of 2.0L (SBR) was used for the cultivation of anammox biomass. The PCR-DGGE and real time PCR were used to monitor and characterize the change in bacterial community diversity in response to different ratios of COD/N applied to the reactor. The results showed that at a concentration of up to 390 mg.L-1 (COD/N 2.8) the removal efficiency was 66%, and the COD concentration of 487 mg L-1 (COD/N 3.5 ) ammonia removal efficiency SBR reduced to 28%, while the nitrite removal efficiency remained high (99%). Nevertheless, when applied to ratio of 5.0, but with COD like to 300 mg.L-1 , of ammonia and nitrite removal efficiency values were high, 84% and 99%, respectively. Thus indicating that the Anammox process can be used in the post-treatment of anaerobic wastewater containing COD concentration below 300 mg.L-1 . When the SBR started to be fed only with the anaerobic effluent plus nitrite (ratio COD/N of 4 to 5), the ammonia removal increased from 55% to 98%, to maximum values of 99%. The identification of bands isolated from the gel DGGE showed that most sequences obtained is related with microorganisms of the phylum Proteobacteria, Chloroflexi and Planctomycetes. Ca. Brocadia sinica was detected in all phases of the study